Can Hip Joint Position affect Quadriceps Muscle Responses during Knee Extension Exercise? - Vieira, Denis César Leite; Dourado, Marco Aurélio Araujo; Ugliara, Lucas; Durigan, Joao Luiz Quagliotti; Schoenfeld, Brad J.; Bottaro, Martim (International Journal of Sports Medicine, 2020)
This study investigated the acute effects of seated and supine knee extension exercise on muscle swelling, torque, and work output. Twelve resistance-trained men performed two isokinetic concentric-only knee-extension training protocols at different hip positions in a counter-balanced order. They completed the knee extension exercise in the seated (hip angle at 85°) and supine (hip angle at 180°) positions. The torque and work output were assessed during each set. Moreover, muscle thickness of the middle and proximal vastus lateralis and rectus femoris were evaluated before and after each protocol and used as an indicator of muscle swelling. Middle rectus femoris and proximal vastus lateralis thickness increased significantly (p=0.01) with no difference between exercise variations. However, the middle vastus lateralis thickness increased (p=0.01) only after the seated knee extension exercise (~7%). Knee extensors’ peak torque and work output were approximately 8% higher (p=0.04) in the seated when compared to the supine hip position. There was a similar decrease in torque and work output throughout both protocols (p=0.98). In conclusion, seated knee extension exercises produced greater torque, work output, and muscle swelling in the vastus lateralis when compared to the supine knee extension exercise.
Keywords: total work; muscle swelling; resistance training; fatigue index; torque